2006
DOI: 10.1007/s10722-004-6150-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Phenotypic Variation in a Germplasm Collection of Carthamus tinctorius L. from the Middle East

Abstract: Phenotypic diversity was assessed for quantitative and qualitative traits in a salt-tolerant subset of the international safflower (Carthamus tinctorius L.) germplasm collection originating from 11 countries in three regions (Central Asia, Southwest Asia and Africa) of the Middle East. Phenotypically, the germplasm, among and within regions, was highly variable, especially for rosette-and yield-related traits. Frequency of desirable variants of seven agronomically important traits ranged from 14% for long rose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…African accessions also lay in the same main cluster, which supports the studies by Johnson et al (1999) and Jaradat and Shahid (2006) that reported the proximity of African accessions to the Mediterranean group. The East Asian group stood out as the most distant.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…African accessions also lay in the same main cluster, which supports the studies by Johnson et al (1999) and Jaradat and Shahid (2006) that reported the proximity of African accessions to the Mediterranean group. The East Asian group stood out as the most distant.…”
Section: Discussionsupporting
confidence: 90%
“…However, the present germplasm did not contain high oleic acid types (Table 2) and, therefore, it is not directly comparable to the core and non-core accessions described by Johnson et al (1999). Other studies (Ashri 1975;Jaradat and Shahid 2006) reported comparable results, showing a wide range of variation in safflower collections for agro-morphological traits as a result of human and natural selection. This suggests good potential for selection in a breeding program (Pascual-Villalobos and Albuquerque 1996).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Genetic diversity of some safflower germplasm has been previously investigated based on the agromorphological traits (Ashri 1975;Jaradat and Shahid 2006), biochemical traits (Han and Li 1992;Fernandez-Martinez et al 1993) and molecular markers including isozymes (Han and Li 1992), RAPDs (Maali Amiri et al 2001;Sehgal and Raina 2005;Vilatersana et al 2005), ISSRs (Ash et al 2003;YuXia et al 2007) and AFLPs (Sehgal and Raina 2005).…”
Section: Introductionmentioning
confidence: 99%